2022
DOI: 10.1186/s12879-022-07558-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic surveillance for multidrug-resistant or hypervirulent Klebsiella pneumoniae among United States bloodstream isolates

Abstract: Background Klebsiella pneumoniae strains have been divided into two major categories: classical K. pneumoniae, which are frequently multidrug-resistant and cause hospital-acquired infections in patients with impaired defenses, and hypervirulent K. pneumoniae, which cause severe community-acquired and disseminated infections in normal hosts. Both types of infections may lead to bacteremia and are associated with significant morbidity and mortality. The relative burden of these two types of K. pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 119 publications
(166 reference statements)
3
30
0
3
Order By: Relevance
“…Another large-scale study in China reported that 36% of screened carbapenem-resistant (CRKp) strains carried the hypervirulence-associated siderophore aerobactin locus [ 17 ]. Other regional studies focused on Singapore [ 18 ], India [ 19 ] and the USA [ 20 ], while the global landscape has also been investigated [ 21 ]. Our work extends the previous reports by exploring in detail the plasmid replicons associated with the CRhvKp genotype, globally.…”
Section: Introductionmentioning
confidence: 99%
“…Another large-scale study in China reported that 36% of screened carbapenem-resistant (CRKp) strains carried the hypervirulence-associated siderophore aerobactin locus [ 17 ]. Other regional studies focused on Singapore [ 18 ], India [ 19 ] and the USA [ 20 ], while the global landscape has also been investigated [ 21 ]. Our work extends the previous reports by exploring in detail the plasmid replicons associated with the CRhvKp genotype, globally.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, all 24 strains that possessed only iucA and/or rmpA/A2 were designated as cKp (Supplementary Table S1). Although, less pragmatic, ascites growth curves further enhance accuracy and murine infection models remain the most accurate means to identify hvKp strains (4, 50). Of note, although commonly used, the Galleria mellonella infection model is unable to differentiate hvKp from cKp (51).…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 4 Structure of carbapenemase gene-carrying plasmids. BRIG images show similarities between plasmid sequences of selected ST395 isolates (central rings) and other published plasmid sequences identified by BLAST (concentric rings colored according to legends).…”
Section: Carbapenemase Genes Were Associated With Different Plasmid R...mentioning
confidence: 99%
“…Klebsiella pneumoniae is an opportunistic pathogen and one of the most common causes of hospital-and community-acquired infections [1]. It has been traditionally differentiated into classic (frequently but not exclusively multidrug-resistant [MDR]) and hypervirulent K. pneumoniae (hvKp) with the latter appearing clinically as mostly antibiotic-susceptible and invasive pathogen able to induce multiple site infection [2][3][4]. However, a recent study revealed that definition boundaries are blurred and that a strict assignation to particular contexts (hospitalor community-associated) not always applies [5].…”
Section: Introductionmentioning
confidence: 99%